(untitled) (Politeja, 2023)
THE ANTI-EUROPEAN DIMENSION OF THE SWISS REFERENDA: THE CASE OF THE SWISS PEOPLE’S PARTY The aim of the article is to analyze the impact of referenda on the increase in the popularity of anti-European sentiments in Switzerland on the example of the activity, in particular during selected referendum campaigns, of the Swiss People’s Party (Schweizerische Volkspartei, SVP). Two research hypotheses will be examined in the article: leading – H1: The Swiss People’s Party uses anti-European slogans to build its position on the political scene; and auxiliary – H2: the Swiss anti-European narrative is primarily related to migration issues. In order to verify or falsify the hypotheses, the following research questions were posed: Q1: Which dimensions of Europeanization arouse the greatest controversy and political disputes in Switzerland?; Q2: What are the programmatic and organizational specifics of the Swiss People’s Party?; Q3: What means does the Swiss People’s Party use in referendum campaigns?; Q4: Are there, and if so, what, specific features of the Swiss anti-European narrative? The answers to the research questions will be contained in the following parts of the text. In the summary, research hypotheses will be resolved and conclusions will be presented.